Performance of obturation techniques in anatomical irregularities located at different thirds of the root canal system - Silverio Vazquez-Alcaraz; Lucia Gancedo-Caravia; Ana Arias; Jaime Bascones (University of São Paulo, 2024)
Abstract This study aimed to compare the quality of root canal obturation (ratio of area occupied by gutta-percha (G), sealer (S), and presence of voids (V)) in different anatomical irregularities (intercanal communications, lateral irregularities, and accessory canals) located at different thirds of the root canal system of mandibular molar replicas. Sixty-seven 3D printed replicas of an accessed mandibular molar were prepared using ProGlider and ProTaper Gold rotatory systems. Three specimens were randomly selected to be used as controls and did not receive further treatment. The rest were randomly distributed in 4 experimental groups to be obturated using either cold lateral compaction (LC), continuous wave of condensation (CW), and core-carrier obturation (ThermafilPlus (TH) or GuttaCore (GC)) (n=16 per group). AHPlus® sealer was used in all groups. The three controls and a specimen from each experimental group were scanned using micro-computed tomography. The rest of the replicas were sectioned at the sites of anatomical irregularities and examined at 30× magnification. The G, S, and V ratios were calculated dividing the area occupied with each element by the total root canal area and then compared among groups using the Kruskal-Wallis test. Voids were present in all obturation techniques with ratios from 0.01 to 0.15. CW obtained a significantly higher G ratio in the irregularity located in the coronal third (0.882) than LC (0.681), TH (0.773), and GC (0.801) (p<0.05). TH and GC achieved significantly higher G ratios in those located in the apical third (p<0.05). The worst quality of obturation was observed in the loop accessory canal with all obturation techniques. Whitin the limitations of this study, it can be concluded that CW and core-carrier obturation are respectively the most effective techniques for obturating anatomical irregularities located in the coronal and the apical third.